Undiagnosed atrial septal defect, complicated with thrombosis, in an adult female - N. V. Belokopytova; V. A. Markov; A. G. Syrkina; V. Kh. Vaizov; T. A. Filippova; S. A. Nazarenko; V. M. Gulyaev (Российский кардиологический журнал, 2008)
.